2006
DOI: 10.2166/wst.2006.597
|View full text |Cite
|
Sign up to set email alerts
|

Development and investigation of a pollution control pit for treatment of stormwater from metal roofs and traffic areas

Abstract: Source control by on-site retention and infiltration of stormwater is a sustainable and proven alternative to classical drainage methods. Unfortunately sedimentary particles and pollutants from drained surfaces cause clogging and endanger soil and groundwater during long-term operation of infiltration devices. German water authorities recommend the use of infiltration devices such as swales or swale-trench-systems. Direct infiltration by underground facilities such as pipes, trenches or sinks without pre-treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…After three pore volumes of ISSW2 flushing, the biochar showed a removal efficiency of approximately 20%, which (while relatively low) is still more significant than the negligible effect achieved by a normal infiltration basin (Birch et al 2005;Walker and Hurl 2002). These results indicated that there is electrostatic attraction of Cr(VI) to the positively charged biochar surface (Dong et al 2011). Effluent chromium concentrations after the final washing with deionized water were less than 0.67 mg=L.…”
Section: Heavy Metalsmentioning
confidence: 90%
“…After three pore volumes of ISSW2 flushing, the biochar showed a removal efficiency of approximately 20%, which (while relatively low) is still more significant than the negligible effect achieved by a normal infiltration basin (Birch et al 2005;Walker and Hurl 2002). These results indicated that there is electrostatic attraction of Cr(VI) to the positively charged biochar surface (Dong et al 2011). Effluent chromium concentrations after the final washing with deionized water were less than 0.67 mg=L.…”
Section: Heavy Metalsmentioning
confidence: 90%
“…Research is ongoing at field installations and laboratories both in the U.S. and in other countries. Active researchers in the water-quality impacts of, and controlling factors for, infiltration through both engineered and natural soils include several researchers in Florida, Villanova University, the University of New Hampshire, North Carolina State University, the University of Maryland, the U.S. EPA Urban Watershed Management Branch (investigations in both New Jersey and Kansas City, Missouri), France, Germany, Norway, Australia, and Switzerland (Davis, 2008;Dechesne et al, 2005;Dechesne et al, 2001;Dierkes et al, 2006;Emerson et al, 2008;Ferguson, 1990;Fischer et al, 2003;Guo et al, 2006;Hathhorn and Yonge, 2005;Hatt et al, 2007;Hatt et al, 2008;Hsieh and Davis et al, 2007a,b;Hunt et al, 2008;Jayasuriya et al, 2007;Kumar et al, 2006;Kwiatkowski et al, 2007;Li and Davis, 2008a, b;Lucas and Greenway, 2008;Marcos et al, 2002;McKenzie and Irwin, 1988;Mikkelsen et al, 1997;Muthanna et al, 2007a,b;Nogaro et al, 2007;Osenbruck et al, 2007;Sample and Heaney, 2006;Sansalone and Glenn, 2007;SRF Consulting Group, 2004;Sun and Davis, 2007;Thomas, 2000;Van Cuyk and Siegrist, 2007;Warnaars et al, 1999;Welker et al, 2006;Zhang and Ross, 2007;Zheng et al, 2006;Zomorodi, 2006).…”
Section: Case Study #4: Effects Of Compost Amendments In Hydraulicallmentioning
confidence: 99%
“…In the case of cement-based samples which absorb large amounts of water in the dry-state, the analyses were conducted for moist material. The preparation of filter samples consisted of placing them in a cell with water for 5 min and subsequent removing the excess water with a vacuum pump set at a pressure of 6.864×10 4 Pa. The process of the removal of water from the filters (gravitational water from pores) lasted 15 min.…”
Section: Methodsmentioning
confidence: 99%
“…Keeping in mind that there are many works confirming the observation regarding the high concentrations of metals dissolved in water [3,4,2] and taking into account the current dense development, increasing traffic and air pollution, one should consider whether rainwater sewage should not be subject to broader legal regulations. In line with the Ordinance of the Minister of Environment dated November 18th, 2014 [5], the requirements regarding rainwater and snowmelt sewage drained by sewage systems and originating mostly from impenetrable surfaces only provide for the allowable content of total suspended solids (100 mg/dm 3 ) and petroleum hydrocarbons (15 mg/dm 3 ) in wastewater introduced to water bodies or soil.…”
Section: /Min 36mentioning
confidence: 99%